Conditions for Synchronization of One Oscillation System - Recke, L.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
Using methods of perturbation theory, we investigate the global behavior of trajectories on a toroidal attractor and in its neighborhood for a system of differential equations that arises in the study of synchronization of oscillations in the mathematical model of an optical laser.